VISUALISASI PERLUASAN DERET FOURIER MENGGUNAKAN SCILLAB - Mega; Salnira (Universitas Cokroaminoto Palopo, 2021)
This paper discusses the use of the Scilab program to visualize the expansion of the Fourier series. As an example, the case is taken from the one used, namely a square wave signal. In this article, we will provide a solution to these cases by solving the related Fourier series using SCILAB software. SCILAB is open source software and can be run on Windows, Mac and Linux operating systems.